Chitosan/Rice Husk-Derived Silica Mixed Matrix Membrane as Potential Separator for Peatwater Purification - Siti Unvaresi Misonia Beladona; Artha Karunia Gresiana Siregar; Midun Efendi Patar Sihombing; Fakhrotun Nisa; Rendy Muhamad Iqbal (Center for Development of Science, Technology and Peatland Innovation (PPIIG), University of Palangka Raya, 2023)
Indonesia has the largest distribution of peatlands worldwide and is spread over Sumatra, Kalimantan, and Papua islands. Peatland is one of the land resources with a hydrological function and can store water in the form of peatwater. Peatwater is brownish-red due to high dissolved organic matter, especially in the form of humic acid and its derivatives, high organic matter content, low pH, and low cation content. Peatwater is classified as polluted water, unsuitable for consumption, and cannot be used directly as drinking, bathing, or washing water. The Mixed Matrix Membrane Fabrication method is expected to be used for peatwater purification by adding silica filler from rice husk ash. Rice husk has a high silica filler content of >90%. The higher the silica level, the better the material absorbs harmful chemical compounds in peatwater, one of which is humic acid.